Variación en la actividad del fotosistema ii de plantas de alcornoque (Quercus suber L.) SOMETIDAS A ESTRÉS HÍDRICO MODERADO Y BAJO DISTINTOS NIVELES DE RADIACIÓN - Jiménez, M D; Pardos, M; Aranda, I; Puértolas, J; Pardos, J A (IV Congreso Forestal Español, 2005)
Se estudió el efecto conjunto de la luz y la disponibilidad hídrica sobre la actividad del fotosistema II (PSII) en plantas de alcornoque (Quercus suber L.) cultivadas en vivero. Se consideraron cuatro niveles de luz (66-70% , 44-50%, 13.5-16% y 5-6%, con respecto a pleno sol) y dos de riego. La mitad de las plantas se regaron a capacidad de campo dos veces por semana (R+: 25-35% de humedad en el sustrato, medido con TDR) y la otra mitad se sometió a dos ciclos de sequía de 51 y 38 días, respectivamente (R-: hasta alcanzar una humedad en el sustrato del 7-10%). Las mediciones se realizaron al amanecer, mediodía y tarde, en cuatro fechas en hojas adaptadas a la oscuridad, empleándose un fluorómetro. Para todos los tratamientos, Fv/Fm presentó los valores más altos al amanecer, disminuyó al mediodía, y experimentó una ligera recuperación por la tarde en los tratamientos de máximo sombreo para la medición del 23 de Julio. Fv/Fm decreció a lo largo del ensayo (al mediodía y por la tarde) hasta alcanzar un mínimo tras finalizar el primer ciclo de sequía.. El riego afectó positivamente la relación Fv/Fm al amanecer solamente en la última medición del primer ciclo. Asimismo se detectó un efecto positivo en los niveles de luz intermedios (13.5% y 16%). Al mediodía y por la tarde, la eficiencia fotoquímica del PSII fue mayor con niveles de luz inferiores al 16%. La eficiciencia cuántica del fotosistema II mostró dos repuestas a las altas radiaciones una caída diaria al mediodía, como un mecanismo de fotoproctección en las horas de mayor radiación y una disminución a lo largo del tiempo que duró el ensayo. El tratamiento de riego no provocó cambios en la eficiencia cuántica del PSII, salvo en una fecha, coincidiendo con la máxima demanda evaporativa. Los tratamientos mayores de luz (>44%) provocaron una pérdida de la eficiencia cuántica del PSII.
Keywords: eficiencia fotoquímica máxima del PSII (Fv/Fm); fluorescencia máxima; fluorescencia variable

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M; Royo, A; Gil, L; Pardos, J A (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)

ESTRUCTURA Y EVOLUCIÓN DE DOS MASAS MIXTAS DE FRONDOSAS PROCEDENTES DE UN ANTIGUO MONTE ADEHESADO - Hermosilla, D; Pardo, F; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
The presence of an important number of deciduous Central European species in Hayedo de Montejo makes it to be considered a singular place in Madrid. Past traditional practices conditioned the present characteristics of this forest. Two mixed deciduous stands were chosen for its study, both formed by a stratum of old-growth trees and another made up of poles. A vegetation inventory was made around twenty old-growth trees. The influence in the structure and evolution of the stand composed by poles was studied. The species of old-growth tree and the distance were relevant on the structure of the stand grown around them.
Keywords: competition; open wood; shade tolerance

Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L; Aranda, I; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential

Micropropagation of juvenile and adult Quercus suber L. - Manzanera, J A; Pardos, J A (Plant Cell, Tissue and Organ Culture, 1990)
This paper describes research on the application of tissue culture techniques to the micropropagation of cork oak (Quercus suber L.), a forest species of ecological and industrial importance in the Mediterranean area. Apical buds and nodal stem segments were employed as initial explants. Their origins were young seedlings, stump sprouts and sprouts formed on cuttings collected from old trees. The action of the mineral medium and growth regulators was studied in the multiplication stage. Media with low concentrations of ions, such as Sommer's or Heller's, are more suitable for growth and proliferation of explants than other media richer in salts. It was also observed that cytokinin (BA) must be present for the culture development. Adding low concentrations of auxin (NAA) to the medium improves the multi- plication rate, especially in vegetative material of adult origin. The auxin type is the most important factor in the promotion of rhizogenesis. The method of application determines the quality of the root system. Treatment with low concentrations of IBA added to the rooting medium gives the best results. High sucrose concentration also improves rooting. Diluting the mineral rooting medium is slightly favourable, although there is no significant difference between it and the standard mineral concentration.
Keywords: Cork oak; micropropagation; Quercus suber; rooting; tissue culture